Relationship Between Urinary Cross-Linked N-Telopeptide of Type-I Collagen and Heel Stiffness Index Measured by Quantitative Ultrasound in Middle-Aged and Elderly Men. Issue 44 (November 2015) - Unknown
Abstract : Abstract: The aim of the present study was to investigate the age-related patterns and the relationship between levels of urinary cross-linked N-telopeptide of type-I collagen (NTx) and heel stiffness index measured by quantitative ultrasound (QUS) in men with a special reference to age groups of aged 40 to 59 years and ≥60 years. A total of 379 men participated in this study. Heel stiffness index (bone mass) was measured by QUS. Spot urine samples were collected, and urinary NTx was measured. The values were corrected for creatinine (Cre) concentration. Stiffness index was significantly lower in men aged ≥60 years compared with men aged 40 to 59 years ( P  < 0.0001). There was no significant difference of Log (NTx/Cre) by 10-year age groups. Multiple regression analysis showed that higher level of urinary NTx/Cre was significantly correlated with lower stiffness index after adjusting for age and body mass index in men aged ≥60 years, but not in men aged 40 to 59 years. Higher rates of bone resorption were associated with lower stiffness index only in elderly men. Our results may indicate a different mechanism of low bone mass among different age groups.